Using artificial intelligence methods and tools in education: Using artificial intelligence methods and tools in education - Ayupov, Ravshan; Kurbonov, Zafar (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Annotaion: Artificial intelligence (AI) has been increasingly applied in learning different subjects and teaching. AI can be used to produce mathematical modelling, computer code, images, or other media in response to users' queries. In education, AI has been implemented in automated assessment, speech recognition, adaptive and personalized provision of educational resources, and more. For example, ChatGPT, as an AI language model, can